Hand-Crafted Features with Simple Deep Learning Architectures for Human Activity Recognition - Albadawi, Yaman Sufian (2024)
A Master of Science thesis in Computer Engineering by Yaman Sufian Albadawi entitled, “Hand-Crafted Features with Simple Deep Learning Architectures for Human Activity Recognition”, submitted in June 2024. Thesis advisor is Dr. Tamer Shanableh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).